PENATAAN SISTEM ALUR TATA NASKAH DINAS ELEKTRONIK DIREKTORAT RUMAH SUSUN KEMENTERIAN PUPR JAKARTA - Susanti, Susanti; Fadholi, Arief (Aksara Public, 2017)
Flats Directorate of The Ministry of Public Works and Public Housing is government agencies in charge of providing flats. The research method used is the method of observation, interview method, and method of study documentation. The official script is the organization of written communication which includes setting the type, format, filling, legitimacy, security, distribution, storage of the official script, and media used in official communication. The implementation of electronic service on the flats directorate of public works and public housing shall be in accordance with Ministerial Regulation No.54 of 2009. Electronic service script is an application used for the storage, distribution, and security of service scripts. The weakness of this application is on inputting outgoing mail, but can be overcome by inputting manually. By the existence of this electronic service script, the work in the Ministry of Public Works and Public Housing is expected can be more effective and efficient.